1996
DOI: 10.1523/jneurosci.16-24-08181.1996
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization Suggests that Retinal and Cortical Inputs Access Different Metabotropic Glutamate Receptors in the Lateral Geniculate Nucleus

Abstract: Glutamate has an important neuromodulatory role in synaptic transmission through metabotropic glutamate receptors (mGluRs) linked to a variety of G-protein-coupled second messenger pathways. Activation of these receptors on relay cells in the lateral geniculate nucleus (LGN) with the agonist trans-(1S,3R)-1-amino-1, 3-cyclopentanedicarboxylic acid produces a membrane depolarization that inactivates the low-threshold Ca2+ spike, causing a transition from burst to tonic response mode. The excitatory effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 42 publications
(63 reference statements)
9
118
0
Order By: Relevance
“…Furthermore, tetanic stimulation of retinogeniculate fibers, but not corticothalamic fibers, mimicked this increase in inhibition (Govindaiah and Cox, 2004). In this study, we clearly demonstrate that type 5 mGluRs are responsible for this action, which is consistent with anatomical data indicating mGluR 5 localization on F2 terminals (Godwin et al, 1996). In contrast to the mGluR 5 -mediated increase in inhibition, we found that activation of mGluR 2,3 decreased sIPSCs in a TTXinsensitive manner.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, tetanic stimulation of retinogeniculate fibers, but not corticothalamic fibers, mimicked this increase in inhibition (Govindaiah and Cox, 2004). In this study, we clearly demonstrate that type 5 mGluRs are responsible for this action, which is consistent with anatomical data indicating mGluR 5 localization on F2 terminals (Godwin et al, 1996). In contrast to the mGluR 5 -mediated increase in inhibition, we found that activation of mGluR 2,3 decreased sIPSCs in a TTXinsensitive manner.…”
Section: Discussionsupporting
confidence: 90%
“…This increase in inhibitory activity resulting from mGluR activation of F2 terminals is insensitive to the Na ϩ -channel blocker tetrodotoxin (TTX) and occurs independent of somatic membrane potential changes in the interneuron (Cox and Sherman, 2000). Considering the diversity of mGluR distribution and variety of mGluR-mediated actions in the thalamus (Godwin et al, 1996;Liu et al, 1998;Cox and Sherman, 1999;Tamaru et al, 2001), we investigated whether specific mGluR subtypes mediate alterations in inhibitory synaptic transmission in the thalamus. Our data suggest that activation of group I mGluRs (mGluR 1,5 ) and group II mGluRs (mGluR 2,3 ) produce distinct physiological actions within the thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the type 1 and type 2 metabotropic receptors seem to have different roles in the thalamic circuitry. Type 1 metabotropic glutamate receptors (mGlu 1 receptors) are found on relay-cell distal dendrites that are postsynaptic to axon terminals from cortical layer 6 [28][29][30] (Figure 1b) and, as will be discussed later, they have been implicated in the cortex-mediated effects on geniculate relay cells observed in anaesthetised cats [31]. More recently, in experiments using slices of adult ferret CNS containing the LGN, a presynaptic metabotropic receptor belonging to group II (mGlu 2 ) has been claimed to reduce cortical feedback to the thalamus selectively (Figure 1b).…”
Section: Elements Of the Circuitrymentioning
confidence: 99%
“…Electrophysiological studies of these pathways have focused on the role of NMDA receptors (see Scharfman et al 1990;Deschenes & Hu 1990; and, latterly, mGlu receptors (see McCormick & Von Krosigk 1992;Golshani et al 1998;Turner & Salt 2000b;Hughes et al 2002). A particular focus has been the function of mGlu1 receptors, as these have been localized postsynaptically in LGN predominantly beneath terminals of corticothalamic bres (Martin et al 1992;Vidnyanszky et al 1996;Godwin et al 1996). Activation of mGlu receptors in thalamic relay neurons causes a slow depolarizing response associated with an increase in membrane resistance, as seen in many other parts of the brain, probably due a reduction in a potassium conductance (McCormick & Von Krosigk 1992;Turner & Salt 1998;Hughes et al 2002), and this has been shown to be mediated speci cally via mGlu1 receptors ( gure 1) (Turner & Salt 2000b;Hughes et al 2002).…”
Section: Cortical Inputs To the Thalmic Relay Nucleimentioning
confidence: 99%
“…This offers a multitude of potential signalling and modulatory possibilities for synaptically and extrasynaptically released glutamate (Kullmann 2000). Within the thalamus the distribution of a considerable number of the various glutamate receptors has been described in some detail (Martin et al 1992;Petralia et al 1996;Godwin et al 1996;Liu 1997;Jones et al 1998;Liu et al 1998;Mineff & Valtschanoff 1999;Neto et al 2000;Mineff & Weinberg 2000;Tamaru et al 2001;Bolea et al 2001). This paper seeks to provide a brief overview of some of the well-known synaptic roles of glutamate receptors in the sensory thalamic relay nuclei, and then on the basis of more recent work to indicate other more speculative synaptic roles and how this might relate to sensory transmission through the thalamus under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%